Efficient Contracts Without Bargaining Over Employment - Martinello, Felice (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1992)
It is often asserted that unions must bargain over employment if efficient contracts are to be achieved. However, efficient outcomes can be reached and supported if the average rate of compensation paid to labour decreases with employment. The author argues that common fringe benefit and layoff and recall provisions should make the average cost of compensation decline with employment. This implies that most firms and unions can reach and support efficient outcomes even though the union negotiates only wages and fringes, and the employer chooses employment unilaterally. Thus the distinction between monopoly models and efficient bargain models of union-firm interaction is not as relevant an empirical issue as previously believed.